Taking locally led climate and security actions seriously in Papua New Guinea - Camille Laville; Almah Tararia; John Cox; Kate Lanyon; Michelle Spearing; Aditi Solanki (ODI Global, 2025)
Ranked among the world's most climate-vulnerable countries, Papua New Guinea is usually portrayed through its risks, from climate-related hazards and environmental pressures to localised insecurity and gender-based violence. But communities across Papua New Guinea are already leading sophisticated responses to climate and human security challenges. Their experience offers insights for international actors rethinking how to partner with local organisations and shift towards more grounded, decolonised humanitarian, development, and peacebuilding (HDP) approaches in fragile and conflict affected contexts.
Keywords: 320; Fragile states; Local leadership; Climate change; Papua New Guinea